Hear Me Write: Does CEO Narcissism Affect Disclosure? - Marquez-Illescas, Gilberto (Journal of business ethics, 2019)
Through earnings announcements, conference calls, and other press releases, corporate executives have an opportunity to frame the narrative of financial disclosures. Numerous studies have shown that textual tone significantly influences stock returns, suggesting that through word choice, upper management may impact market reaction. In this study, we examine the influence of CEO personality traits on corporate disclosures by analyzing the tone of earnings announcements for a sample of Fortune 500 CEOs over nearly two decades. Our hypotheses are twofold: (1) that qualitative disclosures in firms with narcissistic leaders will be biased upward and (2) the bias will moderate as CEOs becomes older. Our empirical results support these hypotheses and suggest that more narcissistic CEOs tend to reinforce their grandiose self-image by issuing more positive earnings announcements but this desire wanes with CEO age. We also find that the stock market response to the tone of the earnings announcement is less pronounced for more narcissistic CEOs, suggesting the market takes into account the bias in narcissistic CEO announcements.